Untitled. (La Celestina: A Feminist Reading of the 'Carpe Diem' Theme, 1992)
A list of books published by Scripta Humanistica is presented which includes "The Comedia and Points of View," by Everett W. Hesse, "The Grand and the Fair: Poe's Landscape Aesthetics and Pictorial Techniques," by Kent P. Ljungquist and "Renaissance and Golden Age Studies in Honor of D. W. McPheeters," edited by Bruno M. Damiani.